2012
DOI: 10.3926/jiem.397
|View full text |Cite
|
Sign up to set email alerts
|

Integration of fuzzy Shannon’s entropy with fuzzy TOPSIS for industrial robotic system section

Abstract: Purpose: The aim of this study is applying a new method for Industrial robotic system selection. Design/methodology/approach: In this paper, the weights of each criterion are calculated using fuzzy Shannon's Entropy. After that, fuzzy TOPSIS is utilized to rank the alternatives. After that we compare the result of Fuzzy TOPSIS with Fuzzy VIKOR method. Then we select the best Industrial Robotic System based on these results. Findings: The outcome of this research is ranking and selecting industrial robotic syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The fuzzy values are expressed as intervals using α -level sets. Jafarnejad Chaghooshi et al (2012) found 0.3 alpha as an appropriate value for the Likert scale (see Table 2). The weighted barriers obtained by fuzzy Shannon's entropy provided in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…The fuzzy values are expressed as intervals using α -level sets. Jafarnejad Chaghooshi et al (2012) found 0.3 alpha as an appropriate value for the Likert scale (see Table 2). The weighted barriers obtained by fuzzy Shannon's entropy provided in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…TOPSIS was first proposed in a crisp version as a linear weighting technique, and after that, it is commonly used to solve the Multi-Criteria decision problems in various engineering and management fields. It works on the principle of geometric distance for selected alternatives; the shortest distance is the positive ideal solution, and the largest is the negative ideal solution [31]. Geometric distances are calculated and summed, and alternatives are chosen based on maximum similarity.…”
Section: Multicriteria Optimizationmentioning
confidence: 99%
“…Among the prominent objective weight approach includes; Standard Deviation weight method (Baruah & K, 1999), Shannon's entropy weight method (Chaghooshi, et al, 2012) which are some referred to as a subjective and objective method, and finally the objective and subjective weight method (Ma, Fan, & Huang, 1999). In this study, we aimed to presents a reliable, easy and straightforward approach for determining criteria weight by using both subjective and objective factors in forming a fuzzy-based AHP model for solving selection, prioritization, and decision-making problems.…”
Section: Criteria Weight Assessment Methodsmentioning
confidence: 99%